Advanced practice nursing: A concept analysis. Issue 2 (12th April 2013) - Dowling, Maura; Beauchesne, Michelle; Farrelly, Frances; Murphy, Kathy
<x xml:space="preserve">Abstract</x> A variety of terms are used to describe advanced practice nursing roles internationally. This has resulted in confusion in terminology around these roles. The aim of this concept analysis was to clarify what is meant by advanced practice nursing internationally, what attributes signify advanced practice nursing and what are its antecedents, consequences, references and related terms. Rodgers's evolutionary method of concept analysis was used. Data sources included Medline, CINAHL, Applied Social Sciences Index and Abstracts (ASSIA), Cochrane Library, Science Direct, SCOPUS, Web of Science, Dissertation Abstracts and DARE as well as relevant nursing texts and professional organization websites. The analysis reveals that there are many different articulations of the advanced practice nursing role outlined in the literature. This variety in terminology hinders developments in advanced practice nursing roles. Consensus on advanced practice nursing definitions, terminology, educational requirements and regulatory approaches is integral to the implementation of the advanced practice nursing role internationally.